DISTRIBUTION AND ACCUMULATION OF THE PERSISTENT ORGANIC POLLUTANTS OCPS VÀ PCBS IN THE COASTAL WATTER OF NORTH VIETNAM - Nghi, Duong Thanh; Thanh, Tran Duc; Quy, Tran Van (Vietnam Journal of Marine Science and Technology, 2014)
The persistent organic pollutants OCPs (Lindan, Aldrin, Endrin, Dieldrin, 4,4-DDE, 4,4-DDD, 4,4-DDT) and PCBs (28, 52, 101, 138, 153, 180) were determined in three components of water, sediment and clam tissues in the coastal watter of North Vietnam in March and August 2011. The results show that the concentrations of ∑OCPs are from 8.79 - 18.35ng/l and ∑PCBs from 8.80 - 254.75µg/l in water; ∑OCPs from 0.36 - 6.81ng/g dry and ∑PCBs from 0.35 - 2.20µg/kg dry in bottom surface sedim-ents; and ∑OCPs from 2.46 - 7.48ng/g dry and ∑PCBs from 2.31 - 52.98µg/kg dry in clam tissues (Meretrix lyrata). The pollutant distribution of ∑OCPs and ∑PCBs at the envoronment components in the coastal sea of North Vietnam is varied by the seasons. By the bio-accumulation factor (BAF) of OCPs from 32.78 - 75.69; and PCBs from 16.28 to 168.37, the bio-accumulation risk of them is ava-ilable in the clam.